Catalytic Performance of Ultrastable Y Type Zeolite and Mg-Modified Ultrastable Y Type Zeolite on the Pyrolysis of Neosinocalamus affinis - Qi, W.Y.; Yang, Y.; Hu, C.W. (Asian Journal of Chemistry, 2013)
Commercially available ultrastable Y type (USY) and Mg-modified USY (Mg-USY) zeolites have been used in the catalytic pyrolysis of Neosinocalamus affinis respectively, in a fixed bed reactor under nitrogen atmosphere at 773 K. The activity tests showed that the liquid yield increased to 56.4 % and 60.1 % with USY and Mg-USY zeolites respectively, in comparison with that of 25.3 % without catalyst. In particular, Mg-USY catalyst exhibited higher liquefaction activity and resulted in low solid residue of 3.5 % comparing to 28.7 % in non-catalytic experiment. In the presence of USY catalyst, acetic acid was observed as the major component and its content reached 72 % from 37.6 % without catalyst. In the presence of Mg-USY catalyst, the content of acetic acid reduced markedly (to just 25.9 %), whereas those of 1-hydroxy-2-propanone, 2-furanmethanol and other moderate-molecular weight compounds increased.